Genomic selection in animals - Weller, Joel Ira (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
The field of whole genome selection has quickly developed into the breeding methodology of the future. As efforts to map a wide variety of animal genomes have matured and full animal genomes are now available for many animal scientists and breeders are looking to apply these techniques to livestock production. Providing a comprehensive, forward-looking review of animal genomics, Genomic Selection in Animals provides coverage of genomic selection in a variety of economically important species including cattle, swine, and poultry. The historical foundations of genomic selection are followed by chapters that review and assess current techniques. The final chapter looks toward the future and what lies ahead for field as application of genomic selection becomes more widespread. A concise, useful summary of the field by one of the world's leading researchers, Genomic Selection in Animals fills an important gap in the literature of animal breeding and genomics.
Historical overview -- Types of current genetic markers and genotyping methodologies -- Advanced animal breeding programs prior to genomic selection -- Economic evaluation of genetic breeding programs -- Least squares, maximum likelihood and Bayesian parameter estimation -- Trait-based genetic evaluation, the mixed model -- Maximum likelihood and Bayesian estimation of QTL parameters with random effects included in the model -- Maximum likelihood, restricted maximum likelihoodand Bayesian estimation for mixed models -- Distribution of genetic effects, theory and results -- The multiple comparison problem -- Linkage mapping of QTL -- Linkage disequilibrium mapping of QTL -- Marker assisted selection, basic strategies -- Genetic evaluation based on dense marker maps, basic strategies -- Genetic evaluation based on analysis of genetic evaluations or daughter-yield evaluations -- Genomic evaluation based on analysis of production records -- Validation of methods for genomic estimated breeding values -- Byproducts of Genomic evaluation analysis: pedigree validation and determination -- Imputation of missing genotypes : methodologies, accuracies, and effects on genomic evaluations -- Detection and validation of quantitative trait nucleotides (QTN) -- Future directions and conclusions.
Includes bibliographical references and indexes.
Description based on print version record and CIP data provided by publisher.
Keywords: Domestic animals -- Genetics; Breeding; TECHNOLOGY & ENGINEERING -- Agriculture -- Animal Husbandry; Breeding; Domestic animals -- Genetics; Animals, Domestic -- genetics; Breeding; Genetic Markers -- genetics; Quantitative Trait Loci -- genetics; Selection, Genetic; Electronic books